Green Expectations: Current Effects of Anticipated Carbon Pricing - Lemoine, Derek (The Review of Economics and Statistics, 2017)
I report evidence that an anticipated strengthening of environmental policy increased emissions. I find that the breakdown of the U.S. Senate's 2010 climate effort generated positive excess returns in coal futures markets. This response appears to be driven by an increase in coal storage. The proposed legislation aimed to reduce U.S. greenhouse gas emissions after 2013, but the legislative process itself may have increased emissions by over 12 million tons of carbon dioxide leading up to April 2010.